Mercury atmospheric emission, deposition and isotopic fingerprinting from major coal-fired power plants in Australia: Insights from palaeo-environmental analysis from sediment cores. (15th October 2021) - Schneider, Larissa; Rose, Neil L.; Myllyvirta, Lauri; Haberle, Simon; Lintern, Anna; Yuan, Jingjing; Sinclair, Darren; Holley, Cameron; Zawadzki, Atun; Sun, Ruoyu
Abstract: Despite Australia's high reliance on coal for electricity generation, no study has addressed the extent to which mercury (Hg) deposition has increased since the commissioning of coal-fired power plants. We present stratigraphic data from lake sediments in the Hunter Valley (New South Wales) and Latrobe Valley (Victoria), where a significant proportion of Australia's electricity is generated via coal combustion. Mercury deposition in lake sediments increased in the 1970s with the commissioning of coal-fired power plants, by a factor of 2.9-times in sediments of Lake Glenbawn (Hunter Valley) and 14-times in Traralgon Reservoir (Latrobe Valley). Sediments deposited after the commissioning of power plants have distinct Hg isotope compositions, similar to those of combusted coals. Mercury emission, estimated using an atmospheric model (CALPUFF), was higher in the Latrobe Valley than in the Hunter Valley. This is a result of higher Hg concentrations in lignite coal, lax regulation and older pollution-control technologies adopted by coal-fired power plants in the Latrobe Valley. Near-source deposition of Hg in Australia is significantly higher than North America and Europe, where better emission controls (e.g. wet flue gas desulfurization) have been in effect for decades. The challenge for Australia in years to come will be to ratify the Minamata Convention and develop better regulation policies to reduce Hg emissions. Graphical abstract: Image 1 Highlights: Coal accounts for 62% of total electricity generated in Australia. Australia-Pacific is the region with the largest gap in Hg knowledge in the world. Hg emissions and deposition in Australia are still increasing since ~1970s. High near-source deposition has identified in urban areas of Victoria. Hg emission regulations in Australia starkly contrast those of counterpart countries.